John Cournos Among the Imagists: Prelude to Petrograd - Smith, Marilyn Schwinn (Journal of Russian American Studies, 2021)
This article explores the overlooked contributions of John Cournos (1881–1966), a Russian-Jewish immigrant to the US, to the Anglo-American Imagist movement and his role as a bridge between English and Russian literary cultures. It examines his relationships with key figures such as Hilda Doolittle (writing under the name H.D.), Richard Aldington, and Ezra Pound, as well as his work translating Russian authors. The study delves into Cournos's time in Petrograd during the 1917 revolution, his poetry inspired by H.D., and his interactions with Russian poet Anna Akhmatova. Highlighting his literary and cultural exchanges, the article situates Cournos within the modernist movement, emphasizing his efforts to blend Russian and Western literary traditions amid geopolitical upheaval. Note: For part 2 of this article see Marilyn Schwinn Smith, “An American in His Native Land: John Cournos in Petrograd,” JRAS 6, no. 1 (2022). [https://doi.org/10.17161/jras.v6i1.17977]